Tonsillitis (Homoeopathy for All, 2021)
There are different types of tonsils such as Palantine tonsils (tonsillapalatina), Adenoids (pharayngeal tonsil or tonsilla pharyngealis) and Lingual tonsils (tonsillalingualis). The tonsils begin developing early in the third month of foetal life. They arise from the endoderm lining, the second pharyngeal pouch, and the mesoderm of the second pharyngeal membrane and adjacent regions of the first and second arches. The two palatine tonsils are found up on the right and left of the back of the throat and adneoids are found high up in the throat. All of these tonsillar structures together are called as Waldeyer’s ring. The palatine tonsils in general are lymphoepithelial organs and positioned in such a way so that they can serve as secondary lymphoid organs initiating immune responses against entering the body. During the fifth or sixth year of life, the tonsils rapidly increase in size, reaching their maximum size at puberty. The epithelium of the tonsils contains specialise cells called as “M cells” that take up the antigens and presents it to helper T lymphocytes. This leads to the lymphocytic proliferation causing the formation of antibodies and immunoglobulins, especially IgA, which is the most critical component of the musical immune system of the upper airway.
Keywords: Palantine tonsils; epithelium; pharayngeal tonsil or tonsilla pharyngealis